FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA BIDAN DALAM MENDUKUNG PROGRAM INISIASI MENYUSU DINI DI ERA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS BIRU- BIRU KEC. BIRU-BIRU KAB. DELI SERDANG TAHUN 2022 - Rosmida, Rosmida Rosmida (Jurnal Inovasi Kesehatan Masyarakat, 2023)
Early initiation of breastfeeding (IMD) Is breastfeeding as soon possible after the baby is born until the first hour. The key to the success of the early breastfeeding initiation (IMD) program is influenced by several factors, namely the age factor, the length of work factor, the education factor, the attitude factor and the training factor. The purpose of this study is to determine the factors related to the performance of midwives in supporting early initiation of breastfeeding programs in the era of the covid-19 pandemic in the work area of the Biru-Biru Public Health Center in 2022. This study used a quantitative method with a cross-sectional design in the work area of the Biru-Biru Public Health with a sample of 29 midwives who handle normal delivaries data were colleted using questionnaires and then analyzed using univariate, bivariate and multivariate analysis and tested by Chi-Square test and multivariate test using logistic regression test with 95% CI. The results of this study were midwives with good performance (51.7), midwives aged > 35 years (58.6%), midwives who had worked for a long time (58.6%), midwives with high education (65.5), midwives with good knowledge (55.2%), midwives who were supportive (51.7%), then midwives who had attented (51,7%). The results of the bivariate analysis showed that the knowledge and training factors thet had a relationship with the performance of midwives in supporting IMD with a p-value >0.05 while the age factors the length of work and factor and education factor did not have a significant relationship with the performance of the midwife in supporting the early have a significant relationship with the performance of the midwife in supporting the early breastfeeding initiation program p-value >0.05. As for the multivariate results, it was found that knowledge is avery dominant variable related to the performance of midwives in supporting the IMD program. The researchers hope that the working area of the Biru-Biru Public Health Center will always maintain good performance in supporting the early initiation of breastfeeding program and provide appropriate rewards ang always attend training on early initiation of breastfeeding.